Safety evaluation of PEGylated MNPs and p-PEGylated MNPs in SD rats - Wen, Hairuo; Huo, Guitao; Qin, Chao; Wu, Hui; Wang, Dan; Dan, Mo; Geng, Xingchao; Liu, Shujie (Scientific reports, 2023)
Polyethylene glycol-coated magnetic nanoparticles (PEGylated MNPs) have demonstrated prominent advantages in cancer diagnosis and hyperthermia therapy. However, there is currently lack of standard mode and sufficient toxicity data for determining the delayed risk of PEGylated MNPs. Nevertheless, the toxicity potentials, especially those associated with the oxidative stress, were ubiquitously reported. In this study, PEGylated MNPs and p-PEGylated MNPs were administrated to SD (Sprague Dawley) rats by single intravenously injection, and various toxicity indicators were monitored till 56 days post-administration for a comprehensive toxicity evaluation. We revealed that both nanoparticles could be rapidly cleared from plasma and enter tissues, such as, liver, kidneys and spleen, and p-PEGylated MNP is less prone to be accumulated in the tissues, indicating a lower toxicity risk. PEGylated MNPs were more likely to up-regulate the expression levels of Th2 type cytokines and trigger inflammatory pathways, but no related pathological change was found. Both MNPs are not mutagenic, while recoverable mild DNA damage associated with the presence of nanoparticles might also be observed. This study demonstrated a research approach for the non-clinical safety evaluation of nanoparticles. It also provided comprehensive valuable safety data for PEGylated and p-PEGylated MNPs, for promoting the clinical application and bio-medical translation of such MNPs with PEG modifications in the cancer diagnosis and therapy.